The MTHFR C677T genetic susceptibility and its role in risk prediction for type 2 diabetic nephropathy in Northern China - Song, Junli; Zhang, Juanjuan; Guo, Qian; Zhao, Qiang (Frontiers in Endocrinology, 2026)
ObjectiveDiabetic nephropathy is a diabetes-induced chronic kidney disease characterized by pathological changes that may involve the entire renal structure and can progress to end-stage renal disease, thereby substantially impairing patients’ quality of life. The MTHFR C677T gene polymorphism has been closely associated with the development of diabetic nephropathy through its regulatory effect on homocysteine levels. Evidence suggests that both the MTHFR C677T genetic variant and other clinical or environmental risk factors may interactively contribute to disease susceptibility. This study investigated the genetic predisposition conferred by MTHFR C677T and its interaction with modifiable risk factors among patients with diabetic nephropathy in northern China, aiming to establish a region-specific risk prediction model for improved early identification and prevention.Material and methodsFrom January 2018 to 2024, a total of 397 patients with type 2 diabetes were selected from the Second Hospital of Shanxi Medical University. Among them, 153 cases were diagnosed as diabetic nephropathy group (DN group), and the remaining 244 cases were control group (N-DN group). The clinical data of these patients were extracted from electronic medical records. The biochemistry index, including homocysteine (Hcy) were collected from the hospital laboratory test system and the polymorphism of MTHFR C677T gene was analyzed by polymerase chain reaction (PCR) test. The risk prediction model of diabetic nephropathy was established by Logistic regression.ResultsMTHFR C677T gene polymorphism was closely related to diabetic nephropathy. The proportion of 677TT genotype (57.52%) and the homocysteine concentration in DN group were significantly higher than those in N-DN group, and the circulating homocysteine concentration in 677TT genotype (17.29 ± 8.95 μmol/L) was significantly higher than that in 677CT genotype (13.08 ± 6.20 μmol/L) and 677CC genotype (12.65 ± 4.35 μmol/L) (P < 0.001). The carriers of MTHFR677CT and MTHFR677TT genotypes could increase 3.298-fold and 12.713-fold risk of having DN respectively compared with the carriers of 677CC genotype.In addition, the diabetic peripheralangiopathy, the diabetic retinopathy, triglyceride(TG), HOMA-IR, HCY(16-30μmol/L), HCY(>30μmol/L), Blood urea nitrogen(BUN), urinary microalbumin creatinine ratio (ACR) were independent risk factors for diabetic retinopathy (OR = 2.462, 4.572, 1.548, 1.133, 1.571,1.379,1.254,1.003). The above eight factors constitute the Nomogram risk prediction model of DN with good test performance and discriminant ability.ConclusionMTHFR C677T genotype, Hcy, the diabetic peripheralangiopathy, the diabetic retinopathy, triglyceride(TG), HOMA-IR, Blood urea nitrogen(BUN), urinary microalbumin creatinine ratio (ACR)diabetic retinopathy were independent factors for diabetic nephropathy, which would help to identify the risk of diabetic nephropathy and provide the basis for the development of diabetic nephropathy control strategies and treatment measures.